SKC 5771 Process Control Laboratory Student's Manual. Second Edition and Revised - Abd Hamid, Mohd Kamaruddin; Mohd Yusof, Khairiyah; Hassim, Mimi Haryani; Baderon, Ahmad Kamal (Universiti Teknologi Malaysia, 2005)
This course introduces students to some features in MATLAB and SIMULINK that usually use for modelling, simulating, and analysing dynamic systems. Virtual Process Control Lab (VPCL) is a program that combines MATLAB and SIMULINK. Students will use this program to study characteristics of some of the various types of feedback and feedforward control action. The course will also provide practice in modelling chemical process using first-order-plus-time-delay (FOTD) transfer function. The model get from FOTD transfer function will be used to design and tune feedback and feedforward control systems. This course will also expose students to areas of process control systems in the chemical industry. It also teaches the students how to control the specific control variables through the use of simple PID control. Students will experience how to perform open loop and closed loop tuning method for specific process. Students will also gain hands-on experience in process control through experiments employing pilot-scale chemical processes.